KIdney aNd blooD prESsure ouTcomes in Childhood Cancer Survivors: Description of Clinical Research Protocol of the KINDEST-CCS Study. (October 2022) - Khondker, Adree; Groff, Michael; Nunes, Sophia; Sun, Carolyn; Jawa, Natasha; Lee, Jasmine; Cockovski, Vedran; Hejri-Rad, Yasmine; Chanchlani, Rahul; Fleming, Adam; Garg, Amit; Jeyakumar, Nivethika; et al.
Background: Approximately 30% of childhood cancer survivors (CCSs) will develop chronic kidney disease (CKD) or hypertension 15 to 20 years after treatment ends. The incidence of CKD and hypertension in the 5-year window after cancer therapy is unknown. Moreover, extent of monitoring of CCS with CKD and associated complications in current practice is underexplored. To inform the development of new and existing care guidelines for CCS, the epidemiology and monitoring of CKD and hypertension in the early period following cancer therapy warrants further investigation. Objective: To describe the design and methods of the KIdney aNd blooD prESsure ouTcomes in Childhood Cancer Survivors study, which aims to evaluate the burden of late kidney and blood pressure outcomes in the first 10 years after cancer therapy, the extent of appropriate screening and complications monitoring for CKD and hypertension, and whether patient, disease/treatment, or system factors are associated with these outcomes. Design: Two distinct, but related studies; a prospective cohort study and a retrospective cohort study. Setting: Five Ontario pediatric oncology centers. Patients: The prospective study will involve 500 CCS at high risk for these late effects due to cancer therapy, and the retrospective study involves 5, 000 CCS ≤ 18 years old treated for cancer between January 2008 and December 2020. Measurements: Chronic kidney disease is defined as Estimated glomerular filtration rate <90 mL/min/1.73 m 2 or albumin-to-creatinine ratio ≥ 3mg/mmol. Hypertension is defined by 2017 American Academy of Pediatrics guidelines. Methods: Prospective study: we aim to investigate CKD and hypertension prevalence and the extent to which they persist at 3- and 5-year follow-up in CCS after cancer therapy. We will collect detailed biologic and clinical data, calculate CKD and hypertension prevalence, and progression at 3- and 5-years post-therapy. Retrospective study: we aim to investigate CKD and hypertension monitoring using administrative and health record data. We will also investigate the validity of CKD and hypertension administrative definitions in this population and the incidence of CKD and hypertension in the first 10 years post-cancer therapy. We will investigate whether patient-, disease/treatment-, or system-specific factors modify these associations in both studies. Limitations: Results from the prospective study may not be generalizable to non-high-risk CCS. The retrospective study is susceptible to surveillance bias. Conclusions: Our team and knowledge translation plan is engaging patient partners, researchers, knowledge users, and policy group representatives. Our work will address international priorities to improve CCS health, provide the evidence of new disease burden and practice gaps to improve CCS guidelines, implement and test revised guidelines, plan trials to reduce CKD and hypertension, and improve long-term CCS health.